Air Pollution-Induced Acute Respiratory Infection - Wibowo, Adityo; Saputra, Tito Tri (Jurnal Kedokteran Universitas Lampung, 2022)
The respiratory system becomes the main target of the harmful effects of major air pollutants including particulate matter (PM), ozone (O3), nitrogen dioxide (NO2), polycyclic aromatic hydrocarbons (PAHs) and volatile organic compounds (VOCs). Particle size is directly related to potential health problems directly in the respiratory tract one of them is respiratory tract infection. The analysis shows a positive correlation between all pollutants and the incidence of acute respiratory infections. The incidence of upper respiratory tract infections, pneumonia, bronchitis and bronchiolitis that occurred in most of the pollutants studied were significantly associated with the incidence of hospitalization due to infection. Keywords: air pollution, infection, respiratory tract